Grüne Sonnen - Illger, Daniel (Cinepoetics, 2020)
In this study, the author develops a poetics of fantasy that calls into question the common interpretation of the genre as politically reactionary and aesthetically dull. On this basis, he argues that the video game has a specific affinity to the genre of fantasy, and he substantiates this thesis by analyzing artistically outstanding games such Dark Souls, Skyrim, and Hellblade.